"Perfidny plan" Elizabeth George jako przykład współczesnej odmiany kryminału = Elizabeth George's "Deception on His Mind" as an example of contemporary crime fiction - Zwolińska, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article discusses the changes in the contemporary detective story, using as an example "Deception on His Mind" by Elizabeth George. The transformations include an extension of the social layer, in the realism which aims to present important problems of the contemporary society, such as racism reinforced by the increasing immigration, in this case of the Pakistanis to England. Using classic devices of detective novel, George makes an accurate diagnosis of the causes conflicting contemporary society in which national minorities induce aversion, which leads to racism, and sometimes also to crime.
Keywords: George, Susan Elizabeth (powieściopisarka amerykańska; 1949- ); literatura amerykańska - tematyka; powieść kryminalna